Maternal inheritance of chloroplast DNA in interspecific crosses of Bromus - Pillay, M.; Armstrong, K.C. (Springer, 2001)
Inheritance of chloroplast DNA (cpDNA) was examined in 41 F1 progeny obtained from the following interspecific Bromus crosses: Bromus arvensis (2n = 14) × B. inermis (2n = 4x = 28); B. arvensis × B. inermis (2n = 8x = 56); B. arvensis × B. erectus (2n = 6x = 42); B. arvensis × B. erectus (2n = 8x = 56); B. arvensis × B. erectus (2n = 10x = 70). Chloroplast DNA of the parental species was digested with BamHI, EcoRI and HindIII and species-specific restriction fragment length polymorphisms were identified by observation of ethidium bromide stained agarose gels as well as by filter hybridization experiments involving heterologous cloned barley cpDNA probes. The stability of these point mutations was verified by examining the cpDNA restriction patterns of at least 28 individual plants raised from seed of each of the parental species. No intraspecific cpDNA variability was detected. All the F1 progeny examined exhibited the cpDNA restriction fragment patterns of the female parent. There was no evidence of any paternal or biparental cpDNA inheritance. The results provided evidence for the uniparental-maternal inheritance of cpDNA in the Bromus crosses examined.